Economic Valuation of Kampar River Capture Fisheries in Buluhcina Village, Siak Hulu District, Kampar Regency, Riau Province - Annisa Rahmadita; Darwis Darwis; Trisla Warningsih (Faculty of Fisheries and Marine, Universitas Riau, 2023)
This study aims to estimate the potential of the Kampar River ecosystem in Buluhcina Village by analyzing the economic value of its utilization for capturing fisheries. This research was carried out in January 2022 at Kampar River, Buluhcina Village, Siak Hulu District, Kampar Regency, Riau Province. The research method used was a survey method, and the cost of respondents used a purposive sampling technique, with 48 respondents. The data needed in this research includes primary data and secondary data. The data analysis used is a resource economic valuation technique, namely the effect on production (EOP) technique. Based on the results of the research that has been done, it shows that the economic value of the Kampar River ecosystem in Buluhcina Village for the utilization of capture fisheries activities is IDR 34,567,921,433.8/year, with a consumer surplus value of IDR 805,779,054.4/year, and the total economic value of capture fisheries activities per m2 is IDR 30,897.4/m2/year